Farmers' perception and awareness towards agriculture insurance as a tool of risk management in Kaski and Chitwan Districts of Nepal - Ghimire, Rabindra; Chapagain, Ram Krishna; Jagari, Dhana Bahadur; Shahi, Lalit Bahadur (The Lumbini Journal of Business and Economics, 2023)
This study aims to assess farmers' awareness and perception towards agriculture risk management and insurance in Nepal's Kaski and Chitwan districts. Despite agriculture being the primary occupation for more than 60% of the population, the contribution of agriculture to GDP remains at 23%. Agriculture insurance is a new concept in Nepal, and the growth of the insurance market has been unimpressive over the past twelve years. The study's sample consists of existing agriculture insurance policyholders who have received or are in the process of receiving claims. Data was collected using a structured questionnaire from 200 respondents in Bharatpur and 200 respondents in Pokhara Metropolitan city, with a five-point Likert scale measuring awareness and perception. Results suggest that farmers are generally aware of the risks associated with agriculture and perceive insurance to be a useful scheme. Trust between farmers and insurance companies is deemed essential for insurance to succeed. Economic and claims-related factors were found to be more influential than family size and education, while the sex and age of respondents were insignificant. The study implies that while insured and claim-recipient farmers have a fair awareness of agriculture insurance, they lack traditional risk management techniques